Scratching the itch with cryo-EM - Maharana, Jagannath (Nat Chem Biol, 2022)
Cryo-EM structures of Mas-related G-protein-coupled receptors (MRGPRs) that are involved in the allergic reaction and itch response reveal structural insights into their activation mechanism, and offer the potential to discover new therapeutic agents for pain and hypersensitivity reactions.